Comparative Effectiveness of Echinocandins vs Triazoles or Amphotericin B Formulations as Initial Directed Therapy for Invasive Candidiasis in Children and Adolescents. (10th August 2021) - Fisher, Brian T; Zaoutis, Theoklis E; Xiao, Rui; Wattier, Rachel L; Castagnola, Elio; Pana, Zoi Dorothea; Fullenkamp, Allison; Boge, Craig L K; Ross, Rachael K; Yildirim, Inci; Palazzi, Debra L; Danziger-Isakov, Lara; et al.
Abstract: Background: Invasive candidiasis is the most common invasive fungal disease in children and adolescents, but there are limited pediatric-specific antifungal effectiveness data. We compared the effectiveness of echinocandins to triazoles or amphotericin B formulations (triazole/amphotericin B) as initial directed therapy for invasive candidiasis. Methods: This multinational observational cohort study enrolled patients aged >120 days and <18 years with proven invasive candidiasis from January 1, 2014, to November 28, 2017, at 43 International Pediatric Fungal Network sites. Primary exposure was initial directed therapy administered at the time qualifying culture became positive for yeast. Exposure groups were categorized by receipt of an echinocandin vs receipt of triazole/amphotericin B. Primary outcome was global response at 14 days following invasive candidiasis onset, adjudicated by a centralized data review committee. Stratified Mantel-Haenszel analyses estimated risk difference between exposure groups. Results: Seven-hundred and fifty invasive candidiasis episodes were identified. After exclusions, 541 participants (235 in the echinocandin group and 306 in the triazole/amphotericin B group) remained. Crude failure rates at 14 days for echinocandin and triazole/amphotericin B groups were 9.8% (95% confidence intervals [CI]: 6.0% to 13.6%) and 13.1% (95% CI: 9.3% to 16.8%), respectively. The adjusted 14-day risk difference between echinocandin and triazole/amphotericin B groups was −7.1% points (95% CI: −13.1% to −2.4%), favoring echinocandins. The risk difference was −0.4% (95% CI: −7.5% to 6.7%) at 30 days. Conclusions: In children with invasive candidiasis, initial directed therapy with an echinocandin was associated with reduced failure rate at 14 days but not 30 days. These results may support echinocandins as initial directed therapy for invasive candidiasis in children and adolescents. Clinical Trials Registration: NCT01869829. Abstract : In this multinational prospective, observational cohort study of children and adolescents with invasive candidiasis, initial directed echinocandin antifungal therapy was associated with an adjusted risk reduction of 7.1 points compared with triazole or amphotericin B formulation antifungals.